2022
DOI: 10.1038/s41529-022-00253-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular polymeric substances of fungal biofilms in mineral attachment and weathering

Abstract: The roles extracellular polymeric substances (EPS) play in mineral attachment and weathering were studied using genetically modified biofilms of the rock-inhabiting fungus Knufia petricola strain A95. Mutants deficient in melanin and/or carotenoid synthesis were grown as air-exposed biofilms. Extracted EPS were quantified and characterised using a combination of analytical techniques. The absence of melanin affected the quantity and composition of the produced EPS: mutants no longer able to form melanin synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Fungi can biosynthesize melanin by two different pathways: either through the L-3,4 dihydroxyphenylalanine (L-DOPA) pathway, which is found primarily in basidiomycetes [ 11 ] and human pathogens [ 12 ], or through the 1,8-dihydroxynaphthalene (DHN) pathway, which is usually found in ascomycetes [ 13 , 14 ], such as fungi belonging to the Sclerotiniaceae family. It is believed that the L-DOPA pathway is spontaneously activated after initiating the oxidation by a laccase [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fungi can biosynthesize melanin by two different pathways: either through the L-3,4 dihydroxyphenylalanine (L-DOPA) pathway, which is found primarily in basidiomycetes [ 11 ] and human pathogens [ 12 ], or through the 1,8-dihydroxynaphthalene (DHN) pathway, which is usually found in ascomycetes [ 13 , 14 ], such as fungi belonging to the Sclerotiniaceae family. It is believed that the L-DOPA pathway is spontaneously activated after initiating the oxidation by a laccase [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…through the study of gene deletion mutants 198,199 (see also ref. 200 in this issue). On the other hand, the application of nm-resolved techniques to the study of microbially weathered surfaces 91,123,192,201 should help characterize imprints of microbial process left behind at mineral surfaces and in the geological record.…”
Section: Challenges and Ongoing Developments Field-lab Discrepancymentioning
confidence: 85%
“…For example, Cladosporium an d Knufia , which can produce extracellular melanin–polysaccharide complexes, which are compounds belonging to the group of extracellular polymeric substances (EPSs) [ 61 , 62 ]. EPSs lend stability to the biofilm by mediating cellular aggregation and bringing the cells in close contact with the substrate via adhesion [ 63 ], encouraging themselves and fungi to attach more strongly to the substrate and deteriorating it at a fast rate. In addition, it was reported that Xylaria were predominantly identified from mycelium particles of a biofilm biomass on the surface of a Mayan building [ 64 ].…”
Section: Discussionmentioning
confidence: 99%